2017
DOI: 10.1144/qjegh2016-136
|View full text |Cite
|
Sign up to set email alerts
|

Glacio-marine clay resistivity as a proxy for remoulded shear strength: correlations and limitations

Abstract: Please check this proof carefully for errors, once it is published online no further changes can be made. In particular check that figures, tables and equations are correct.Please note that acknowledgements and funding information are now defined under separate headings. Please check that our copyeditors have correctly assigned the text under the correct heading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…5) show more spread than Long et al. (2017), but unlike their data set that consisted exclusively of marine clay, our lab samples included other types of sediment. Even though we observed some systematic bias in our airborne electromagnetic (AEM)‐derived resistivity models compared with resistivity CPT (RCPT) measurements, the AEM generally has the same strengths and weaknesses of in situ RCPT in terms of identifying quick and non‐brittle material.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…5) show more spread than Long et al. (2017), but unlike their data set that consisted exclusively of marine clay, our lab samples included other types of sediment. Even though we observed some systematic bias in our airborne electromagnetic (AEM)‐derived resistivity models compared with resistivity CPT (RCPT) measurements, the AEM generally has the same strengths and weaknesses of in situ RCPT in terms of identifying quick and non‐brittle material.…”
Section: Discussionmentioning
confidence: 82%
“…Our exploratory data analysis confirms that the petrophysical relationship between remoulded shear strength and resistivity of glaciomarine clay at our study site is consistent with observations at other locations in Scandinavia. Long et al.’s (2017) review showed the same general trends throughout sites in Norway: material below 10 Ωm was never quick and only occasionally brittle; and material between 10 and 100 Ωm could either be quick clay or stable, unleached marine clay mixed with coarser sediment. Our data (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the resistivity signature of quick clay is non-unique. Whereas material that with very high (>100 Ωm) or very low (<5 Ωm) can be ruled out as quick, marine clay with intermediate resistivities may either be leached, quick marine clays, or marine clays that was mixed with coarser sediments or which has undergone weathering processes [46]. Intrusive geotechnical investigations are needed to resolve this ambiguity.…”
Section: Quick Clay Modellingmentioning
confidence: 99%